Evaluation and Follow Up Solitary Pulmonary Nodule - Wiwi Pertiwi Hasimin; Muhammad Yamin Sunaryo (Jurnal Respirasi, 2019)
With the increased utilisation of chest computed tomography, solitary pulmonary nodules are increasingly being identified. It is not clear whether this is of an increased incidence, increased awareness (ie, recognition of an abnormality as opposed to considering it an inconsequential finding), or increased identification because of an increasing prevalence of CT imaging. Whatever the reason, how to approach these patients is an issue that increasingly confronts clinicians. Through the evaluation of patient risk factors combined with computed tomography characteristics of solitary pulmonary nodules, including size, growth rate, margin characteristics, calcification, density and location; a clinician can assess the risk of malignancy. This literature will describe the evaluation and follow-up of pulmonary nodules based on several guidelines and how they apply to populations in Asia because of the different patient populations compare with Western countries ranging from risk factors, high infectious factors that can be confounding diagnosis and different genetic predispositions.